2016
DOI: 10.3390/v8060172
|View full text |Cite
|
Sign up to set email alerts
|

Lambda gpP-DnaB Helicase Sequestration and gpP-RpoB Associated Effects: On Screens for Auxotrophs, Selection for RifR, Toxicity, Mutagenicity, Plasmid Curing

Abstract: The bacteriophage lambda replication initiation protein P exhibits a toxic effect on its Escherichia coli (E. coli) host, likely due to the formation of a dead-end P-DnaB complex, sequestering the replicative DnaB helicase from further activity. Intracellular expression of P triggers SOS-independent cellular filamentation and rapidly cures resident ColE1 plasmids. The toxicity of P is suppressed by alleles of P or dnaB. We asked whether P buildup within a cell can influence E. coli replication fidelity. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 92 publications
0
8
0
Order By: Relevance
“…Several of the rpoB mutants, B1 (Q148P), B8 (L571Q), C4 (ΔGEV440-442V), D2 (R451S) and D6 (G537C) had been shown to confer cellular resistance to the highly toxic λ gpP, while C1 (P564L) and C10 (R529H) remained P-sensitive [ 37 ]. Except for B1, both P R and P S mutants, suppressed CII toxicity at 39 °C (cell viabilities: 594[cII], 0.03; rpoB [cII]: B1, 0.003; B8, 0.65; C1, 0.96; C4, 0.15; C10, 0.14; D2, 0.95; D6, 0.11) and 42 °C.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several of the rpoB mutants, B1 (Q148P), B8 (L571Q), C4 (ΔGEV440-442V), D2 (R451S) and D6 (G537C) had been shown to confer cellular resistance to the highly toxic λ gpP, while C1 (P564L) and C10 (R529H) remained P-sensitive [ 37 ]. Except for B1, both P R and P S mutants, suppressed CII toxicity at 39 °C (cell viabilities: 594[cII], 0.03; rpoB [cII]: B1, 0.003; B8, 0.65; C1, 0.96; C4, 0.15; C10, 0.14; D2, 0.95; D6, 0.11) and 42 °C.…”
Section: Resultsmentioning
confidence: 99%
“…What is responsible for CII toxicity? It was shown that the single base substitution G537C responsible for rpoB D2 [ 37 ] can completely suppress CII toxicity and plasmid loss at the highest level of cII expression at 42 °C (with cell viability of 0.95 at 39 °C and no plasmid loss), while reducing but not eliminating CII complementation at 39 °C. This suggests that both CII toxicity and plasmid loss depend upon a binding interaction between CII and E. coli RNA polymerase holoenzyme, or a direct interaction with the β-subunit encoded by rpoB .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Each of these alleles was examined for their ability to complement the growth of a λ O amber mutant(s) in trans . We have explored the influence of O:P interactions on cell growth and toxicity, since the expression of P by itself, using the same system, is highly toxic [ 25 , 36 ]. These studies reveal that some alleles of O with internal deletions can complement as well or better than O + and that the co-expression of O-P , or of O with portions of the N-terminal end of P , prevents an ability of O to complement in trans .…”
Section: Introductionmentioning
confidence: 99%